Persepsi Siswa Terhadap Pelayanan Pegawai Tata Usaha di SMK Negeri 1 Kecamatan Guguak Kabupaten Lima Puluh Kota - Fatma Wila; Hadiyanto Hadiyanto; Rifma Rifma; Lusi Susanti (Universitas Negeri Padang, 2021)
This existance of problems that the reseachers encountered in Vocationl High School 1, Guguak District, Lima Puluh Kota District related to administrative staff service that were still not optimal was the background of this study, so that were still students who were not satisfied with the services received by these pupils. The purpose of this study is to describe student’s perceptiions of administrative staff services in terms of transparency, reliability, responsiveness, and physical evidence. The type of this research is descriptiive usiing a quantiitative approoach. Data were collected using a questionnaire, the data sources in this study were all students and female students in the Vocational High School 1, Guguak District . The results showed that : 1) students perceptions of administrative staff services in Guguak District 1 Vocational High School, seen from the transparancy aspect, were good with an average score of 3,94, 2) Student’s perceptions of administrative staff services in Public Vocational High School 1 Guguak Subdistict, seen from the reliability aspect , is good with an average score of 3,94, 3) Student’s perceptions of administrative staff services at the Vacational High School 1, Guguak District , seen from the responsiveness aspect, are good with an average score of 4,20. 4) Student’s perceptions of administrative staff service in Vocational High School 1, Guguak District, seen from the aspect of physical evidence it is goods with an average score of 4,13, 5) Student’s perceptions of administrative staff services in Public Vocational High School 1, Guguak Subdistrict, Lima Puluh Kota Regency is already good with an average score of 4,11.